2016
DOI: 10.4081/audiores.2016.154
|View full text |Cite
|
Sign up to set email alerts
|

Transient Noise Reduction in Cochlear Implant Users: A Multi-Band Approach

Abstract: A previously-tested transient noise reduction (TNR) algorithm for cochlear implant (CI) users was modified to detect and attenuate transients independently across multiple frequency-bands. Since speech and transient noise are often spectrally distinct, we hypothesized that benefits in speech intelligibility can be achieved over the earlier single-band design. Fifteen experienced CI users (49 to 72 years) were tested unilaterally using pre-processed stimuli delivered directly to a speech processor. Speech intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…The MCTR algorithm used here differs from most transient-reduction algorithms 373 described in the literature (with the exception of Dyballa et al, 2016), in that transients are 374 detected and attenuated in a frequency-selective manner. Thus, attenuation of transients 375 dominated by high frequencies did not affect the gain applied to low frequencies, and vice versa.…”
mentioning
confidence: 99%
“…The MCTR algorithm used here differs from most transient-reduction algorithms 373 described in the literature (with the exception of Dyballa et al, 2016), in that transients are 374 detected and attenuated in a frequency-selective manner. Thus, attenuation of transients 375 dominated by high frequencies did not affect the gain applied to low frequencies, and vice versa.…”
mentioning
confidence: 99%
“…The noise type used was a “cafeteria” noise, consisting of a mix of clattering dishes, and reverberant multi-talker babble. The noise was identical to the one described previously ( Dyballa et al 2016 ). To the normal-hearing ear, the noise was acoustically perceived as a loud clatter with a damped murmur in the background.…”
Section: Methodsmentioning
confidence: 99%
“…TNR mb divides the input audio signal into four frequency bands (0 to 1000, 1000 to 2000, 2000 to 4000, and >4000) and independently applies the detection and attenuation to these bands using the same detector as TNR bb-std . The attenuations are proportional to the band-specific transient amplitudes and vary from 10 to 30 dB ( Dyballa et al 2016 ). The authors reported significantly better speech intelligibility with TNR mb-std in transient noise than with the TNR switched off (TNR off ), and it significantly outperformed TNR bb-std .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, if both the attack and release time are made very short, so as to reduce the gain for intense transient sounds, this can lead to reduced overall sound quality (Tan & Moore, 2004). Several transient noise reduction (TNR) algorithms have been developed to mitigate these problems (Digiovanni et al, 2011;Dingemanse et al, 2018;Dyballa et al, 2015Dyballa et al, , 2016Hirszhorn et al, 2012;Keshavarzi, Baer, et al, 2018;Korhonen et al, 2013). Digiovanni et al (2011) studied the effects of two different TNR algorithms on speech intelligibility and subjective ratings of sound comfort, sound quality, and speech understanding for hearing-impaired (HI) participants.…”
mentioning
confidence: 99%